Optically stimulated luminescence ages of the Hengyu site and their implications for anthropogenic activities in the Fuzhou Basin, South China - Jin, Jianhui; Huang, Yunming; Zhang, Yong; Li, Zhizhong; Fan, Xuechun; Ling, Zhiyong; Zheng, Fei; Cheng, Yan; Xu, Xiaolin; Li, Zhixing; Zhang, Wenjing (Journal of quaternary science, 2019)
ABSTRACT The chronologies of few Neolithic sites in the lower reaches of the Min River of China have been well investigated for the middle to late Holocene. In this study, the Hengyu Neolithic site in Fujian Province, South China, which has significant archaeological remains, was dated using blue‐stimulated optically stimulated luminescence (OSL) and accelerator mass spectrometry radiocarbon (AMS14C) techniques. The results, comprising nine OSL and three AMS14C ages through the Neolithic sequence, provide new evidence towards understanding the relationship between environmental evolution and human activities in the middle to late Holocene in the Fuzhou Basin and coastal areas of South China. The ages of the site deposits vary from 6.83 to 1.67 ka and can be divided into two main phases: the Keqiutou–Tanshishan culture period and the Bronze culture period. In contrast, the persistent periods of ancient human activities at the Hengyu site seem to correspond to regional sea‐level changes and the East Asian winter monsoon as a secondary factor, which can affect human activities through sea‐level impacts. The warm and high sea level conditions provided a liveable environment for the ancient humans of Fujian and even South China. The ages of two building column bases are linked to the early stage of the Han dynasty, suggesting a potentially favourable habitation environment; that is, ancient humans occupied and settled this area for the long term within this time period, which is consistent with sea‐level changes and palynology records. Copyright © 2019 John Wiley & Sons, Ltd.